Jansenismo francês num códice da Biblioteca Nacional de Portugal - Santos, Cândido dos (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
The purpose of this paper is to demonstrate the infl uence of Jansenism, namely through French authors, in Codex 13049 from the National Library of Portugal (BNP). The codex is composed of six parts, three of which are Portuguese translations of the work Défense de lʼÉglise Romaine contre les calomnies translations of the work Défense de lʼÉglise Romaine contre les calomnies (BNP). The codex is composed of six parts, three of which are Portuguese des Protestans, by French Jansenist Dom Gabriel Gerberon (1628-1711). Protestants (Calvinists) accused the Roman Church of being Pelagian. Dom Gerberon attempts to illustrate the differences between Catholic, Protestant and Pelagian doctrines concerning the mysteries of Predestination and Grace. The work includes a collection of dialogues between Deodatus and Romano that could be seen as a sort of Jansenist Catechism. The Codex also reveals the infl uence of other Jansenist authors such as Vivien de Laborde and Jérome Besoigne.